2013
DOI: 10.1177/0148607113510182
|View full text |Cite
|
Sign up to set email alerts
|

Motilin and Gastrin Secretion and Lipid Profile in Preterm Neonates Following Prebiotics Supplementation

Abstract: A prebiotics enriched formula resulted in significant surge of motilin relating to reduced gastric residue, compared with a common preterm formula. Mean cholesterol change was lower, while LDL was not increased in the prebiotics group, compared with the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 48 publications
1
19
1
Order By: Relevance
“…As regards efficacy, there are conflicting reports about the use of prebiotic ingredients in this specific population group. Absence of results were reported by Modi et al [57] when GOS/FOS at the usual dose of 0.8 g/100 mL was fed to a large (79 subjects) cohort of preterm infants, with the aim to obtain a total milk intake of 150 mL/kg; on the contrary, the same prebiotic preparation [58] provided an increase of stool frequency, an improvement of feeding tolerance and reduction of bilirubin level; Indrio et al [51,52] reported positive outcomes for gastric motility, results confirmed by Dasopoulou et al [50]. Absence of positive outcomes was also reported for the use of the pAOS/GOS/FOS mixture formulation in a series of papers by Westerbeek and coworkers [69][70][71]88], by van den Berg et al [73] and Niele et al [77], with the exception of positive outcomes recorded for stool gut microbiota characteristics [66,68,89]..…”
Section: Effects On Preterm Infantsmentioning
confidence: 81%
See 2 more Smart Citations
“…As regards efficacy, there are conflicting reports about the use of prebiotic ingredients in this specific population group. Absence of results were reported by Modi et al [57] when GOS/FOS at the usual dose of 0.8 g/100 mL was fed to a large (79 subjects) cohort of preterm infants, with the aim to obtain a total milk intake of 150 mL/kg; on the contrary, the same prebiotic preparation [58] provided an increase of stool frequency, an improvement of feeding tolerance and reduction of bilirubin level; Indrio et al [51,52] reported positive outcomes for gastric motility, results confirmed by Dasopoulou et al [50]. Absence of positive outcomes was also reported for the use of the pAOS/GOS/FOS mixture formulation in a series of papers by Westerbeek and coworkers [69][70][71]88], by van den Berg et al [73] and Niele et al [77], with the exception of positive outcomes recorded for stool gut microbiota characteristics [66,68,89]..…”
Section: Effects On Preterm Infantsmentioning
confidence: 81%
“…Dasopoulou et al [50] published a study similar to those of Indrio et al [51,52] Vandeplas et al [54] using the same sample size than above assessed the impact of this combination among formula, fermented formula and prebiotic on colic. After 4 weeks of treatment the research group demonstrated a reduced overall incidence of infantile colic in group 3 GOS/FOS +50% FERM, better than in group 1 and 4, suggesting a dose response for the fermented formula.…”
Section: Studies Assessing the Effects Of Combinations Of Prebiotic Imentioning
confidence: 99%
See 1 more Smart Citation
“…Futher studies are warrant to verify in large group of infected infants below one month of age, because gut hormones play an important role in the adaptation of the immature neonatal gut and their production is modulate by a lot of risk factors connected with infection. New studies on gastrin and motilin secretion in preterm neonates (in which sepsis and necrotizing enterocolitis were noted), following prebiotics supplementation indicate, that a prebiotics enriched formula had any effect on sgc [23].…”
Section: Discussionmentioning
confidence: 99%
“…This may be the consequence of increased energy harvest by intestinal bacteria and enhanced nutrient absorption by enterocytes. It is worth mentioning that Dasopoulou et al found that the supplementation of infant formula with scGOS/lcFOS resulted in significantly lower cholesterol and low-density lipoprotein levels compared with preterm neonates fed with standard formula (Dasopoulou et al, 2015). It is worth mentioning that Dasopoulou et al found that the supplementation of infant formula with scGOS/lcFOS resulted in significantly lower cholesterol and low-density lipoprotein levels compared with preterm neonates fed with standard formula (Dasopoulou et al, 2015).…”
Section: Gastrointestinal Transit and Resorption Of Nutrientsmentioning
confidence: 99%